Generations on the Polish labor market in the context of competences needed in the economy based on knowledge and 4.0 - Kryk, Barbara (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The Polish labor market employs employees from four generations, but not all of them have the competences required by the knowledge-based economy and the 4.0 economy. According to the author, adjusting employees’ competences to the requirements of the modern labor market is determined, among others, by specificity of generations. Their features, attitudes, values and job expectations affect competences, which generates quantitative and qualitative changes in the labor market. Therefore, it was decided to check which generations of employees have the competences most appropriate to the needs of these economies. Aim: The aim of the paper is to assess the adjustment of competences of four generations of Polish employees to the competences required of employees of the knowledge-based economy and the 4.0 based on a literature review. Results: Research results confirm that generations Y and C have competences best suited to the modern labor market. Moreover, they indicate areas of skills shortages that require support in order to adjust the requirements of the labor market. The added value is provided by a self-developed list of differences between the labor markets of the knowledge-based industrial economy and 4.0 (there was no such was not such a broad list comparison in the literature for the three types of economies) and synthetic assessment of the key competences of four of generations of employees in the context of KBE and economy 4.0 based on a literature review.